Analisis Perilaku Konsumen Rokok Mild Berdasarkan Persepsi dan Sikap - Fayola Issalillah; Rafadi Khan Khayru; Didit Darmawan; Muhammad Wayassirli Amri; Sri Purwanti (Journal of Trends Economics and Accounting Research, 2021)
In Indonesia, there are quite a lot of cigarette consumers. For entrepreneurs, especially those engaged in cigarette products, the large number of cigarette consumers is a business opportunity that has the potential to continue to grow. This can be seen from the increasing number of new cigarette brands launched in the market and supported by the large number of people who smoke. The desire to consume mild cigarettes can be influenced by various factors such as consumer perceptions and attitudes. The purpose of this study is to analyze the role of consumer perceptions and attitudes towards consumer behavior which in this case is the decision to purchase mild cigarettes. This research was conducted in the center of Sidoarjo City. Research subjects are consumers of mild cigarettes. This study used 173 respondents as a sample. The study used data obtained from distributing questionnaires. The data obtained will then be processed using SPSS with multiple linear regression data analysis techniques. The results show that consumer perceptions and attitudes have a significant effect on consumer behavior